English Teaching Practices at Local Primary Schools: Teachers’ Problems and Solutions - Nurfadila, Sari; Eryansyah, Eryansyah; Amrullah, Amrullah (Universitas Jambi, Indonesia, 2024)
This research aimed to find out what problems English teachers had in teaching English as local content at primary school and how these problems were addressed. The research employed a case study design grounded in qualitative methods. The participants were four English teachers at two different public primary schools in the subdistrict of Prabumulih Timur. Research data were collected through questionnaires, interviews, and observations. In analysing the collected data, percentage analysis was used for questionnaires and thematic analysis for interviews and observations. The questionnaire’s results revealed a number of noteworthy findings, such as the lack of technological knowledge among some teachers and the students' perception of elementary school textbooks as excessively difficult and boring. Interviews and observation also uncovered other difficulties, including work load, time constraints, classroom management, technology use, teaching administration, and the complexity of the topic. These results suggest that in order for EFL teachers to successfully teach English in public elementary schools, they must have techniques to deal with every issue that arises. To help instructors teach as effectively as possible, the government must strike a balance between the amount of time allotted for studying English at SDN/MIN and the subject matter that needs to be covered.